Development and validation of the Scale of the Tendency Toward the Flexitarian Diet - Gumus, Aylin Bayindir; Durmaz, Sevinc Eser; Acik, Murat; Ozturk, Ebru (Pontificia Universidade Catolica Campinas, 2025)
Objective This study aimed to develop the Scale of the Tendency Towards the Flexitarian Diet (STFLEX) to measure the leaning towards the flexitarian diet. Methods The researchers created a 31-draft scale. Two items with lower content validity ratios were excluded from the scale. A 29-item draft was submitted through an online survey for data collection. Healthy adult volunteers attended from different Internet websites in T & uuml;rkiye. Scale items measuring individuals' predisposition to follow aflexitarian diet. The itemswere evaluated with contentvalidity following the Lawshe method. Confirmatory factoranalyseswere conducted totestconstructvalidity. The Cronbach's alpha coefficient was calculated for reliability. Results Based on the validation analyses, no item was excluded from the item whole. Because of the factor analysis, the scale was divided into four subdimensions (economic reasons, macro-environment, environmental sustainability, and meat consumption). The developed STFLEX showed good compliance statistics, as established with the confirmatory factor analysis fit indices (chi 2/df = 1.593, CFI = 0.967, TLI = 0.960, NFI = 0.916, RMSEA = 0.053), and high reliability (Cronbach's alpha = 0.958). Conclusion The STFLEX is a reliable and valid tool for measuring the tendency toward the flexitarian diet, and it can be used in studies.
Desenvolvimento e validação da Escala de Tendência à Dieta Flexitariana
Keywords: Diet; plant-based; Dietary patterns; Reliability and validity; Sustainable eating; Vegetarian diet